Variations of endonasal anatomy: relevance for the endoscopic endonasal transsphenoidal approach - van Lindert, Erik J. (Springer Vienna, 2010)
BACKGROUND: The endoscopic endonasal transsphenoidal approach (EETA) to the pituitary is performed by ear, nose, and throat (ENT) surgeons in collaboration with neurosurgeons but also by neurosurgeons alone even though neurosurgeons have not been trained in rhinological surgery. PURPOSE: To register the frequency of endonasal anatomical variations and to evaluate whether these variations hinder the progress of EETA and require extra rhinological surgical skills. METHODS: A prospective cohort study of 185 consecutive patients receiving an EETA through a binostril approach was performed. All anatomical endonasal variations were noted and the relevance for the progress of surgery evaluated. RESULTS: In 48% of patients, anatomical variations were recognized, the majority of which were spinae septi and septum deviations. In 5% of patients, the planned binostril approach had to be converted into a mononostril approach; whereas in 18% of patients with an anatomical variation, a correction had to be performed. There was no difference between the ENT surgeon and the neurosurgeon performing the approach. Complications related to the endonasal phase of the surgery occurred in 3.8%. Fluoroscopy or electromagnetic navigation has been used during 6.5% of the surgeries. CONCLUSION: Although endonasal anatomical variations are frequent, they do not pose a relevant obstacle for EETA.